Sistem Penjaminan Mutu Eksternal di SD Negeri Petompon 03 Semarang (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study analyzes the implementation of the External Quality Assurance System within the context of enhancing educational quality. Facing globalization challenges, quality education is crucial, yet significant obstacles like access disparities, teacher qualifications, and curriculum relevance persist. Consequently, robust education systems and quality assurance mechanisms are vital. This case study aims to elaborate on the concept of educational quality, outline EQAS mechanisms, and analyze its application at SD Negeri Petompon 03 Semarang, thereby providing comprehensive insights into quality assurance components and their operationalization. Employing a qualitative approach with a case study design, this research integrates both secondary data (regulatory documents, BAN-PDM accreditation data) and primary data (in-depth interviews with school and education agency stakeholders, observations, and internal document analysis). Qualitative data analysis involves reduction, presentation, and drawing conclusions verified through triangulation. Findings reveal that EQAS at SD Negeri Petompon 03 encompasses periodic evaluations by school supervisors and BAN-PDM. Although the school achieved a "B" accreditation rating, the 2019 evaluation highlighted areas needing improvement, specifically in the Standard for Educators and Education Personnel (regarding the percentage of S1-educated and certified teachers) and School Facilities and Infrastructure. Remedial efforts include strengthening internal quality assurance leadership, implementing professional development programs for teachers (PPG), gradually improving facilities, and utilizing National Assessment data. Overall, EQAS implementation has made positive contributions, but sustained collaboration between the school and the education agency remains essential for continuous quality improvement.